Design, analysis and production of temperature sensor using microstereolithography technique - Waqar, Tayyab (My University, 2022)
Sensör teknolojilerindeki hızlı gelişmeler, son birkaç on yılda nanoelektronik yapı üretim tekniklerimde yapılan teknolojik ilerlemeden olumlu yönde etkilenmiştir. Mikro fabrikasyon tekniklerinin kullanılması performans ve güvenilirliği artırırken diğer yandan fiziksel boyut, hacim, ağırlık ve maliyetin azaltılmasına da yardımcı olmuştur. 3D baskı teknikleri ve ekipmanları alanındaki sürekli gelişmeler, elektronik yapı, devre ve cihaz imalatı alanında ve diğer birçok alanda kullanılmasını sağlamıştır. Bu ilerleme, silikon bazlı mikro ve hatta nano elektronikler kullanılarak bir entegrasyon yoluyla sensörlerin potansiyel olarak yazdırılmasını mümkün kılmıştır. Halihazırda bu tür cihazların ve yapıların üretimi ve ambalajlanması, ağır bir şekilde yavaş olabilen ve önemli işleme gereksinimleri içerebilen litografiye bağlıdır. Bu tezin temel amacı, İki Foton Polimerizasyon tabanlı 3B baskı tekniği yöntemlerinden biri olan Doğrudan Lazer Yazı üretim yöntemini kullanarak sıcaklık algılayıcı bir IDT yapısı tasarlamak, analiz etmek ve imal etmektir. Buna ek olarak, geliştirilen algılama yapısının Sonlu Elemanlar Analizi ve modellenmesi ve sıcaklıktaki değişimler kullanılarak karakterizasyonu bu çalışmanın en önemli amaçları arasındadır. Yüzey akustik dalgası kullanılarak sıcaklık algılamanın çalışma prensibi detaylı olarak araştırılmış ve son imalat sürecinden önce algılama yapısının tasarımını optimize etmek için sonlu eleman tabanlı çalışmalar yapılmıştır. Simülasyon yoluyla elde edilen sonuçlar ışığında IDT yapıları üretilmiştir. Üretilen yapılar daha sonra üretim sırasında herhangi bir kusur olup olmadığını kontrol etmek için elektron mikroskobu kullanılarak incelendi. Daha sonra, bir vektör ağ analizörü kullanılarak rezonans frekans tepkileri ölçüldü. Buna ek olarak, fabrikasyon algılama yapılarının karakterizasyonu gerçekleştirilmiştir. Son olarak, bu çalışmanın ön sonuçları sunulmuş ve simülasyon ve pratik testler ile karşılaştırması yapılmıştır.

The rapid advancements in sensor technologies have been affected positively by the technological progress that has been made my nanoelectronics structure fabrication techniques over the last few decades. The use of micro-fabrication techniques has increased the performance and reliability, while on the other hand, it has also helped in reducing the physical size, volume, weight, and cost. Continuous developments in the field of 3D printing techniques and equipments have enabled its usage in the field of electronics structures, circuits, and devices fabrication as well beside many other fields. This advancement has enabled the potential printing of sensors, via integration using silicon-based micro or even nanoelectronics. Currently, the manufacturing and packaging of such devices and structures are heavily reliant on lithography, which can be slow and can involve substantial processing requirements. The main aim of this thesis is to design, analyze and fabricate a temperature sensing IDT structure by employing the Direct Laser Writing fabrication method which is one of the forms of Two-Photon Polymerization based 3D printing technique methods. In addition to that, Finite Element Analysis and modeling of the developed sensing structure and the characterization using changes in temperature are among the most important objectives of this study. The working principle of temperature sensing using surface acoustic wave was researched in detail and finite element-based studies were performed to optimize the design of the sensing structure before the final fabrication process. In the light of the results obtained through simulation, the IDT structures were fabricated. The fabricated structures were then inspected using an electron microscope to check for any defects during the fabrication. Afterward, their resonant frequency response was measured using a vector network analyzer. In addition, the characterization of the fabricated sensing structures was performed. Finally, the preliminary results of this study are presented and the comparison with the simulation and practical testing is performed.
Keywords: 2PP; Acoustic wave; Additive manufacturing; Akustik dalga; Direct Laser Write; Direk Laser Basımı; IDT; Katmanlı üretim; Mechatronics; Mekatronik; MEMS; Rayleigh dalgası; Rayleigh wave; SAW Sensor; SAW Sensörü; Sıcaklık; Surface temperature; Surface waves; Temperature; Yüzey dalgaları; Yüzey sıcaklığı